Investigation of The Limiting Behavior of The Sequence of Density Ratios in A Family of Non-Central t-Distribution - Sunardi Wirjosudirdjo (Institute for Research and Community Services (LPPM) ITB, 1964)
Abstract. Let X1, X2,